G-protein-coupled Receptor Kinase Interactor-1 (GIT1) Is a New Endothelial Nitric-oxide Synthase (eNOS) Interactor with Functional Effects on Vascular Homeostasis - Liu, Songling (American Society for Biochemistry and Molecular Biology, 2012)
Endothelial cell nitric-oxide (NO) synthase (eNOS), the enzyme responsible for synthesis of NO in the vasculature, undergoes extensive post-translational modifications that modulate its activity. Here we have identified a novel eNOS interactor, G-protein-coupled receptor (GPCR) kinase interactor-1 (GIT1), which plays an unexpected role in GPCR stimulated NO signaling. GIT1 interacted with eNOS in the endothelial cell cytoplasm, and this robust association was associated with stimulatory eNOS phosphorylation (Ser(1177)), enzyme activation, and NO synthesis. GIT1 knockdown had the opposite effect. Additionally, GIT1 expression was reduced in sinusoidal endothelial cells after liver injury, consistent with previously described endothelial dysfunction in this disease. Re-expression of GIT1 after liver injury rescued the endothelial phenotype. These data emphasize the role of GPCR signaling partners in eNOS function and have fundamental implications for vascular disorders involving dysregulated eNOS.